Down to the Bone - Granik, Debra; MacDonough, Michael; Farmiga, Vera; Dillon, Hugh; Jordan, Clint (Lionsgate Home Entertainment, 2006)
Drama starring Vera Farmiga as Irene, a woman who realises her marriage is getting stale and who is finding it hard to raise her two sons whilst hiding her addiction to cocaine. Desperate to get her life back together she decides to get off the drugs for the sake of her husband and children. However this becomes a greater challenge with the onset of winter and a new love entering her life. [www.amazon.co.uk]